Pengaruh Ulasan & Rating Online terhadap Impulsive Buying dengan Intervening Trust - Lutfiana, Retno Arum Angen (Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to evaluate the influence of online customer review and online customer rating on impulsive buying decisions through trust among Shopee users purchasing the moisturizer product